2013
DOI: 10.1007/s00204-013-1063-z
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of interleukin-1 beta attenuates silica-induced lung inflammation and fibrosis in C57BL/6 mice

Abstract: The inflammation and fibrosis induced by silica dust are considered to be substantial responses in silicosis progression. Interleukin-1 beta (IL-1β) plays an important role in silica-induced lung inflammation, but the mechanisms that underlie the influence of IL-1β on the progression of silicosis remain unclear. In this study, the role of IL-1β in silica-induced inflammation and fibrosis was evaluated by administering a suspension of 2.5-mg silica dust, either with or without 40 μg anti-mouse IL-1β monoclonal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(77 citation statements)
references
References 34 publications
5
70
0
1
Order By: Relevance
“…The role of cytokines and oxidative stress markers, IL-1b and inducible iNOS, respectively, has been reported in studies investigating the pathogenesis of pulmonary toxicity induced by crystalline silica [42,43]. Mice genetically deficient (knockout) in IL-1b or iNOS showed significantly reduced silicotic lesions [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of cytokines and oxidative stress markers, IL-1b and inducible iNOS, respectively, has been reported in studies investigating the pathogenesis of pulmonary toxicity induced by crystalline silica [42,43]. Mice genetically deficient (knockout) in IL-1b or iNOS showed significantly reduced silicotic lesions [44].…”
Section: Discussionmentioning
confidence: 99%
“…Mice genetically deficient (knockout) in IL-1b or iNOS showed significantly reduced silicotic lesions [44]. The generation of IL-1b [43] and nitric oxide [44] was associated with the development of lung lesions including granuloma formation and fibrosis in experimental silicosis. In this study of ASD toxicity, IL-1b and iNOS expression were also demonstrated in both acute and chronic inflammatory lesions, suggesting that secondary released cytokines and oxidative stress generated in lesions may be involved in the development of the acute and chronic lung lesions induced by the intratracheally instilled ASD particles [45].…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that instilled silica increases IL-1β release in BALF and neutralizes IL-1β attenuated silica-induced pulmonary inflammation and fibrosis. 38 An earlier study has reported that the levels of pro-inflammatory cytokines, such as IL-1β and IFN-γ, are significantly increased in BALF following NiONP exposure. 39 In the current study, we found that NiONP exposure significantly increased IL-1β protein expression in BALF and mRNA expression in AMs.…”
mentioning
confidence: 98%
“…However, anakinra and etanercept made the R837-and CpG-induced increase in embryo resorption to decline almost completely. These findings suggested that anakinra and etanercept may be useful to prevent pregnancy failure in cases of combined bacterial and viral infection (Chen et al 1998, McCall et al 2012, Guo et al 2013.…”
Section: Discussionmentioning
confidence: 99%